PENGARUH MODEL EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 026793 BINJAI - Siregar, Khopipah Indah; Prawijaya, Septian (JS (JURNAL SEKOLAH), 2024)
Abstract : The Effect of Example Non Example Model on the Learning Outcomes of IPAS Class V Students of SDN 026793 Binjai. This research aims to determine the effect of the Example Non Example learning model on the learning outcomes of IPAS (Integrated Science) for fifth-grade students at SDN 026793 Binjai. The research design used is a Quasi-Experimental Design in the form of Non-Equivalent Control Group Design. The population of this study is all fifth-grade students at SDN 026793, totaling 48 students. The research sample was taken using total sampling technique, consisting of class V-A as the experimental group and class C as the control group. Data were collected using a 20-item multiple-choice test of IPAS Topic C "Bagaimana Aku Tumbuh Besar" The research results obtained the average pre-test score for the experimental group was 46.67, increasing to 83.54 in the post-test. Meanwhile, the average pre-test score for the control group was 47.08, increasing to 75.21 in the post-test. The data analysis technique used hypothesis testing (t-test) using independent samples t-test, obtaining a sig. value (2-tailed) < 0.05, hence Ha is accepted and Ho is rejected. It can be concluded that the Example Non Example model influences the learning outcomes of IPAS for fifth-grade students on the topic of "Bagaimana Aku Tumbuh Besar".Keywords: Example Non Example, IPAS Learning Outcomes Abstrak : Pengaruh Model Example Non Example terhadap Hasil Belajar IPAS Siswa Kelas V SDN 026793 Binjai. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Example Non Example terhadap hasil belajar IPAS siswa kelas V di SDN 026793 Binjai. Jenis Penelitian yang digunakan adalah Quasi Experimental Desain berbentuk Non-Equivalent Control Group Design. Populasi penelitian ini adalah seluruh siswa kelas V SDN 026793 yang berjumlah 48 siswa. Sampel penelitian ini diambil menggunakan tekhnik sampling total yang terdiri dari kelas V-A sebagai kelas eksperimen dan kelas V-B sebagai kelas kontrol. Data dikumpulkan menggunakan test hasil belajar sebanyak 20 butir soal IPAS Topik C Bagaimana Aku Tumbuh Besar yang berbentuk pilihan berganda. Hasil penelitian memperoleh nilai rata-rata pre-test kelas eksperimen sebesar 46,67 dan meningkat menjadi 83,54 saat diberikan post-test. Sedangkan nilai rata-rata pre-test kelas kontrol sebesar 47,08 dan meningkat menjadi 75,21 saat diberikan post-test. Tekhnik analisis data yaitu menggunakan uji hipotesis (uji t) menggunakan uji independent samples t-test memperoleh nilai sig. (2-tailed) < 0,05 maka Ha diterima dan Ho ditolak. Dapat disimpulkan bahwa model Example Non Example berpengaruh terhadap hasil belajar IPAS siswa kelas V materi Topik C Bagaimana Aku Tumbuh Besar.Kata kunci: Example Non Example, Hasil Belajar IPAS